The Effectiveness Of Hand Sanitizer N-Hexane Fraction Of Avocado Leaves (Persea americana Mill.) Against Bacteria Staphylococcus aureus and Escherichia coli - Vivi Eulis Diana; Evi Ekayanti Ginting; Eliana Fitri (Science Midwifery, 2020)
Background; Infectious diseases are one of the main public health problems in developed and developing countries. Most infectious diseases are caused by microorganisms in the form of bacteria, including Staphylococcus aureus and Escherichia coli. Avocado leaves contain, among other things, flavonoids, polyphenols, alkaloids, saponins, quercetin which are antibacterial. Previous research stated that the flavonoid content contained in avocado leaves (Persea americana Mill.) has antifungal, antiviral and antibacterial activity. Purpose; to determine the formulation and effectiveness test of the n-hexane fraction of avocado leaf (Persea americana Mill.) hand sanitizer against Staphylococcus aureus and Escherichia coli bacteria. Method; This type of research is experimental and aims to develop a hand sanitizer gel preparation product from avocado leaf fractions and test its antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria. Avocado leaf fraction gel formulations were made with fraction concentrations of 5%, 10%, 15% with CMC-Na as the base. For gel results, physical tests were carried out including: organoleptic test, homogeneity test, pH test and spreadability test. Result; The antibacterial activity test was carried out using the agar diffusion method and for the positive control Nuvo hand sanitizer gel was used and DMSO was used for the negative control. The results of this study indicate that the avocado leaf fraction gel has antibacterial activity with an average diameter of the inhibition zone for a gel fraction concentration of 5% (9.45mm, 9 mm), a gel fraction concentration of 10% (9.63 mm, 9.16 mm). , 15% concentration (10.3 mm, 9.8 mm), positive control (8.56 mm, 8.78 mm), and a negative control (0 mm, 0 mm). A concentration of 5% is classified as a strong inhibitory power, a concentration of 10% or 15% is classified as a strong inhibitory power. The positive control was classified as moderately inhibitory, and the negative control did not provide antibacterial activity. Conclusion: Avocado leaf fraction (Persea americana Mill.) has antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria, with the highest inhibition zone at a concentration of 15% and the most effective concentration based on statistical tests is 5%.